Data Mining and Predictive Analytics for E-tourism - Antonio, Nuno (2022)
Antonio, N., De Almeida, A., & Nunes, L. (2022). Data Mining and Predictive Analytics for E-tourism. In Z. Xiang, M. Fuchs, U. Gretzel, & W. Höpken (Eds.), Handbook of e-Tourism (pp. 1-25). Springer, Cham. https://doi.org/10.1007/978-3-030-05324-6_29-1